Tolerance of Rice Plants to Mercury Stress through the Application of Exopolysaccharide-Producing Bacteria - Yummama Karmaita; Munif Ghulamahdi; Didy Sopandie; Hariyadi Hariyadi; Irdika Mansur (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study aimed to analyse the effect of exopolysaccharide-producing (EPS) bacteria on rice growth and yield under mercury stress induced by applying 40 mg HgCl? to each bucket containing 10 kg of soil. The research was conducted on a plastic-house scale in Sijunjung Regency, West Sumatra, Indonesia, from December 2025 to March 2026. The experimental design used was a two-factor factorial completely randomized design. The first factor was rice variety (IR 64 and Sertani). The second factor was no bacterial treatment versus bacterial consortium treatment (Priestia megaterium, Priestia aryabhattai, Pseudarthrobacter defluvii, and Burkholderia vietnamiensis). Each treatment was replicated three times. The results showed that there was no interaction between bacterial treatment and the tested rice varieties. In the IPB 9G and Sertani cultivars, the bacterial consortium increased tillers per hill, total productive tillers per hill, root dry weight, and shoot dry weight. It also increased 1,000-grain weight, filled-grain weight per panicle and per hill, and the number of filled grains per panicle. Compared with the control, the bacterial consortium treatment increased filled grain weight per hill by 25.76% in the IPB 9G variety and by 60.77% in the Sertani variety. Based on PCA, the variables contributing to PC1 were panicle length (PL) (0.925), PW (0.869), and PH (0.859). Correlation analysis showed that panicle weight (PW) and number of filled grains per panicle (NFGPP) (r = 0.98). Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land